PERCEPTION OF PHARMACEUTICAL PROFESSIONALS ON IMPLEMENTATION OF PHARMACEUTICAL CARE IN PRIMARY HEALTH CARE - Shio, Marina Tiemi (Revista Brasileira de Educação e Saúde, 2021)
Introduction: Pharmaceutical Care in Primary and Specialized Health Care was standardized by Ordinance No. 1,918 / 2016 approved by the Municipal Health Secretariat of São Paulo. The role of the pharmacist is important for expanding health care and improving adherence to drug treatment for patients. Objective: The research evaluate the perception of pharmaceutical professionals regarding Pharmaceutical Care after the implementation of the Ordinance in the Primary Health Care and Specialty Network. Methods: An online questionnaire was applied before and after the regulation of the Ordinance. Thirty-two pharmacists answered the questionnaires. The opinions of the pharmaceutical professionals regarding the types of interventions used, their ability to intervene, generate good results and the patients' trust for the pharmacist were similar before or after the regulation of the Pharmaceutical Care Ordinance. However, after the standardization of the ordinance, there was an increased participation of pharmaceutical professionals in the meetings of the multidisciplinary team. During the meeting, there was an increase of the feedback concerning the improvement of pharmacotherapy. Pharmaceutical professionals reported that they felt more inserted in the multidisciplinary team (81.25%) and it is necessary an improvement their professional skills (87.50%), as well as an academic updating (96.88%). The implementation of Pharmaceutical Care, according to Ordinance No. 1,918 / 2016, brought pharmacists closer to patients using the Unified Health System (SUS) and to the multidisciplinary team of their Health Unit, enabling a better monitoring of the patient with polypharmacotherapy.